Determinants of Private Investment in Pakistan - Sakr, Khaled (IMF Working Papers; Working Paper ;, 1993)
This paper investigates the determinants of private investment in Pakistan with special emphasis on the impact of government investment. Using annual data for the period 1973/74-1991/92, it is estimated that private investment was positively correlated to GDP growth, to credit extended to the private sector, and to government investment. When government investment is disaggregated into Its infrastructural and noninfrastructural components, the latter is found to be negatively correlated with private investment.